Tension Pneumocephalus Related to Radiotherapy for Nasopharyngeal Carcinoma - Esther Jimenez-Jimenez; Sebastià Sabater Martí; M. Victoria Villas (Case Reports in Oncological Medicine)
Introduction. Tension pneumocephalus (TP) is a very rare complication related to radiotherapy for nasopharyngeal carcinoma (NPC). Case Presentation. A 46-year-old man was admitted to the hospital with an altered mental status and aqueous rhinorrhea for several hours of evolution. The computed tomography (CT) scan showed TP, a defect in the skull base and nasocranial fistula. The patient was receiving a second course of radiotherapy for local relapse. With medical treatment the patient recovered neurological status but died two days later. Discussion. In our knowledge, only 4 cases with similar characteristics have been reported in the literature. This is the first case report of TP during radiotherapy. TP was an abrupt and rapid process with neurological impairment for hours of evolution without suspicious osteoradionecrosis (OR) in previous scan images. The defect in the skull base could be due to a rapid disappearance of the tumor. The appearance of aqueous rhinorrhea and neurological symptoms must be viewed as signs of alarm.